Challenging educational expectations of the social web: a web 2.0 far? - Neil Selwyn (Nordic Journal of Digital Literacy, 2015)
This short position paper reconsiders the exaggerated expectations that currently surround the social web and education within many sections of the education technology community. In particular four popular assumptions of the social web are challenged, namely: (i) expectations of enhanced participatory learning; (ii) expectations of enhanced equality of opportunity; (iii) expectations of learner affinity and interest; and (iv) expectations of freedom from proprietary constraints. The paper contends that many of these expectations stem from a tendency for education technology researchers and writers to over-value seemingly ‘new’ informal uses of the social web, whilst downplaying unequal power relations between individual learners and formal processes of education. The paper concludes that educationalists and technologists alike should strive to look beyond the rhetoric of the social web, and develop realistic and critical understandings of the ‘messy’ realities of social web technologies and education.